IN SILICO IDENTIFICATION OF BREADFRUIT PLAN COMPOUNDS (Artocarpus atilis) AGAINST ANGIOTENSIN-CONVERTING ENZYME 2 AS A CANDIDATE MODEL OF COVID-19 INHIBITORS - Fauzi, Muhammad; Soemarie, Yulistia Budianti; Hasniah (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
The spread of COVID-19 has continued to grow rapidly worldwide. This disease is characterized by the presence of severe respiratory syndrome disorders in humans. The ACE2 receptor is the gateway for the COVID-19 virus to target cells, where it is expressed in airway epithelial and vascular endothelial cells. Breadfruit (Artocarpus altilis) contains active flavonoids. Flavonoid derivatives found in breadfruit include artonin-E, cycloaltilisin-7, cycloaltilisin, isocyclomorusin, cyclomorusin, cyclomulberrin, isocyclomulberrin, cyclocommunal, morusin, quercetin and artocarpin. This study aimed to determine the flavonoid derivative of breadfruit (Artocarpus altilis), which has the most effective potential against the ACE2 receptor, as a candidate inhibitor of the COVID-19 virus in silico. The results showed that of the eleven flavonoid derivatives of breadfruit (Artocarpus altilis) tested, 3 compounds gave the lowest binding affinity value, namely cycloaltilisin -8.79 kcal/mol, cyclomulberrin -8.95 kcal/mol, and artocarpin -9.30. kcal/mol compared to Chloroquine -7.67 kcal/mol and Hydroxychloroquine -7.22 kcal/mol. The predicted results of the Lipinski Rule of Five showed that the 3 compounds and the comparison drug met the Ro5 rule. The compounds cycloaltilisin, cyclomulberin, and artocarpine have antiviral activity, as indicated by the Pa value in the range of 0.5<Pa<0.7. Cycloaltilisin, cyclomulberin and artocarpine are the most effective compounds to be developed as candidates for COVID-19 inhibitors. Keywords: Breadfruit, ACE-2, Covid-19, In Silico